The Δ1-pyrroline-5-carboxylate synthetase family performs diverse physiological functions in stress responses in pear (Pyrus betulifolia) - Ma, Changqing; Wang, Mengqi; Zhao, Mingrui; Yu, Mengyuan; Zheng, Xiaodong; Tian, Yike; Sun, Zhijuan; Liu, Xiaoli; Wang, Caihong (Frontiers in Plant Science, 2022)
Δ1-Pyrroline-5-carboxylate synthetase (P5CS) is the rate-limiting enzyme in proline biosynthesis in plants. Although P5CS plays an essential role in plant responses to abiotic and biotic stresses, its biological functions remain largely unclear in pear (Pyrus betulifolia). In the present study, 11 putative pear P5CSs (PbP5CSs) were identified by comprehensive bioinformatics analysis and classified into five subfamilies based on their preferred substrates. Segmental and tandem duplications were responsible for the evolution and expansion of the PbP5CS gene family. Numerous cis-acting elements related to plant development, hormones, and/or stress responses were identified in the promoters of PbP5CS genes. To investigate the regulatory roles of PbP5CS genes in response to abiotic and biotic stresses, gene expression patterns in publicly available data were explored. The tissue-specific expressional dynamics of PbP5CS genes indicate potentially important roles in pear growth and development. Their spatial and temporal expression patterns suggest key functions in multiple environmental stresses. Transcriptome and real-time quantitative PCR analyses revealed that most PbP5CS genes exhibited different expression patterns in response to abiotic stresses (e.g., drought, waterlogging, salinity-alkalinity, cold, and heat) and biotic stresses (e.g., Alternaria alternate and Gymnosporangium haraeanum). The results provide insight into the versatile functions of the PbP5CS gene family in stress responses. The findings may assist further exploration of the physiological functions of PbP5CS genes for the development and improvement of stress tolerance in pear and other fruits.